The corporate income tax : international trends and options for fundamental reform - Devereux, Michael P.; Sorensen, Peter B.; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2006)
This paper discusses the future of the corporate income tax in an integrating world economy. The first part of the paper reviews some important trends in corporate taxation across the OECD area. The second part discusses the role of the corporation tax, laying out guidelines for corporate tax reform and considering some alternatives to existing corporate income taxes. In discussing options for fundamental reform, two sets of concerns are addressed. The first represents the traditional aims of a tax on corporate income. Essentially the traditional aim has been to design a tax system which raises revenue as efficiently as possible - that is, which minimises distortions to the location and scale of investment, to the sources and uses of finance, and to the choice of legal form. These distortions have been the subject of study for many years, and many proposals for reform have been made. One of the most popular and enduring ideas has been to tax only economic rent: in a traditional framework such a tax would not be expected to have any effect on investment or financing decisions. There is also a second set of concerns. Part of this concern has also been the subject of study for many years - the relationship between the personal and corporate sectors, and in particular, the possibility of tax avoidance by shifting income between the two sectors.
Economic Papers